Effectiveness of point-of-use and pitcher filters at removing lead phosphate nanoparticles from drinking water. (1st August 2021) - Doré, Evelyne; Formal, Casey; Muhlen, Christy; Williams, Daniel; Harmon, Stephen; Pham, Maily; Triantafyllidou, Simoni; Lytle, Darren A.
Highlights: Six point-of-use and pitcher filters were challenged with 100 µg/L Pb-PO4 nanoparticles. The three faucet-mounted POU filters removed between 44.6 and 64.6% of total Pb. The three pitcher filters removed between 10.9 and 92.9 % of total Pb. The POU and pitcher filters had difficulty removing the Pb nanoparticles under certain conditions. Pb nanoparticles should be considered when certifying POU and pitcher filters. Abstract: Orthophosphate (PO4 ) addition is a common corrosion control treatment used to lower lead (Pb) concentrations at the consumer's tap by forming relatively insoluble Pb-phosphate (Pb-PO4 ) minerals. However, some Pb-PO4 particles that can form in drinking water are mobile nanoparticles (i.e., 0.001-0.1 µm) that have the potential to reach the tap. Point-of-use (POU) or pitcher filters are often used to manage risks during distribution system upsets, when corrosion control treatment is not optimized, or following Pb service line replacements. To abide by industry convention, POU and pitcher filters must be NSF/ANSI-certified for Pb reduction (NSF/ANSI-53) using a test water containing dissolved Pb and large Pb particles. Certification for particulates reduction (NSF/ANSI-42) is done using a test water that contains particles, but not leaded particles. To address the lack of testing for Pb nanoparticles, this study challenged six certified commercially available faucet-mounted POU (3) and pitcher (3) filters with aqueous suspensions of Pb-PO4 nanoparticle. For the water quality investigated, the Pb particles formed ranged between 0.016 and 0.098 µm, based on scanning electron microscopy, transmission electron microscopy, and dynamic light scattering analysis. These particles represented 98.5% of total Pb in suspension. The total Pb removals were between 44.6 and 65.1% for the POU filters, and between 10.9 and 92.9% for the pitcher filters. The electron microscopy results confirm that Pb-PO4 nanoparticles passed through the filters. The findings can inform future efforts to re-examine the test waters used in the certification challenge tests. Graphical abstract: Image, graphical abstract